The impact of global factors on stock market movements in emerging market economies - Axel Jochem; Stefan Reitz (Intereconomics, 2014)
Global factors are becoming increasingly important as a cause of international capital flows. It is nearly impossible for some countries to protect themselves from outside influences on their financial markets. This paper investigates the extent to which various global factors such as stock market volatility, international liquidity and global interest rate levels impact on the effective financial market exchange rates of selected emerging market economies. These results are compared with effects on the financial market exchange rates of the United States, the United Kingdom and Germany.
Keywords: 330; Kapitalmobilität; Marktliquidität; Internationaler Finanzmarkt; Börsenkurs; Ansteckungseffekt; Wechselkurs; Schwellenländer